Widal test interpretation in COVID-19 patients: a study from a dedicated COVID center - Bineeta Kashyap; Nadeem Ahmad; Rajat Jhamb; Kapil Chaudhary (Shahid Beheshti University of Medical Sciences, 2024)
Background: There have been several outbreaks of coronaviruses including the present SARS-CoV-2 outbreak. The clinical presentation of COVID-19 infection may mimic febrile phase of dengue fever, typhoid fever, malaria, and several other diseases. During the COVID-19 pandemic, more number of typhoid cases were reported. The goal of this study was to determine the seropositivity of the widal test amongst RT-PCR (Real Time Polymerase Chain Reaction) positive COVID-19 patients. Methods: A cross-sectional study was done on RT-PCR positive COVID-19 patients at the Department of Microbiology, Guru Teg Bahadur Hospital, a designated COVID-19 hospital in Delhi, India between March 2020 to January 2021 and April 2021 to July 2021. Results: Out of 136 samples received for widal testing,58 patients showed evidence of recent infection (significant TO titre ≥ 128) and  32 patients (significant titre TH ≥256)  may have been in the convalescent stage of enteric fever. An increased number of female patients showed widalseropositivity as compared to males. In our study, 50 (36.76%) and 26 (19.11%) patients with significant titre (TO ≥128; TH ≥256) were less than 40 years of age. Conclusion: Documenting the prevalence of typhoid fever, especially during the COVID-19 pandemic, is very difficult. Serological results like widal tests can be misleading, sometimes; due to the cross reacting antigens and the endemicity. Cases of co-infections or false positivity amidst an ongoing pandemic are likely to get unreported unless the clinicians are mindful of the rare occurrence of co-infections by various pathogens. Our study concludes that careful surveillance and interpretation of widal seropositivity in COVID-19 patients is crucial, especially in endemic settings.